The predictable collateral consequences of nucleosynthesis by spallation reactions in the early solar system - Leya, I; Halliday, A; Wieler, R (Institute of Physics Publishing, 2003)
Ever since their first discovery in 1960, the origin of the relatively short-lived radionuclides, now extinct but alive in the early solar system, has been under debate. Possible scenarios are either nucleosynthetic production in stellar sources, e.g., asymptotic giant branch stars, Wolf-Rayet stars, novae, and supernovae, with subsequent injection into the solar nebula, or the production by spallation reactions in the early solar system. Here we present model calculations for the second scenario, the production of the relatively short-lived radionuclides by solar energetic particle events at the start of the solar system. The model is based on our current best knowledge of the nuclear reaction probabilities. In addition, the modeling depends on the relative fluence contribution of protons, 3He, and 4He in the solar particle events as well as on their energy distribution. The relative fluence contribution is the only free parameter in the system. Finally, the modeling depends on the chemical composition assumed for the irradiated target. The model simultaneously describes the observed solar system initial ratios 7Be/9Be, 10Be/9Be, 26Al/27Al,41Ca/40Ca, 53Mn/55Mn, and 92Nb/93Nb. In the framework of the local production scenario, the concordance of measured and modeled data for nuclides with half-lives ranging from 53 days up to 36 Myr enables us to put some stringent constraints on possible calcium-aluminum-rich refractory inclusion (CAI) production and its timing. One important requirement in such a scenario is that the material forming most of the CAIs must have experienced a surprisingly homogenous particle fluence. CAIs showing evidence for live 10Be, 26Al, 41Ca, 53Mn, and 92Nb close to the inferred solar system initial ratios would have to have been irradiated within ∼1 Myr. Much more stringent would be the time constraint for the one CAI for which formerly live 7Be has been reported. Such CAIs would have to have been irradiated for less than about 1 yr. Such a short timescale requires flux densities as high as ∼10 16 cm-2 s-1. To allow further tests of the local production scenario, we also predict solar system initial ratios for 14C/12C, 22Na/23Na, 36Cl/35Cl, 44Ti/48Ti, 54Mn/55Mn, 63Ni/60Ni, and 91Nb/93Nb, whose correlated shifts in the daughter isotopes would help to further test the local production scenario.